A. -3x+5+7-4x
-3x-4x+5+7
-7x+12
-7x+12-5x+17
-7x-5x+12+17
-12x+29
B. -5*(x+2)= -5x-10
-6x-1+ (-5x-10)= -6x-5x-1-10=
-11x-11
Answer: X= 16
Step-by-step explanation:
Answer:
-1.8 =x
Step-by-step explanation:
12(x+3)=-8x
Distribute
12x +36 = -8x
Subtract 12x from each side
12x-12x +36 = -8x-12x
36 = -20x
Divide each side by -20
36/-20 = -20x/-20
-9/5 = x
Changing to decimal form
-1.8 =x
2x + 3y + 2(x - y) - 3x
First you apply the distributive property:
2x +3y + 2(x) - 2(y) - 3x
2x + 3y +2x - 2y - 3x
The you combine like terms:
2x + 2x - 3x +3y - 2y
4x - 3x + y
x (x could also be 1x) + y (y could also be 1y)
The answer is x + y or 1x + 1y
54/35 is the answer to this question